Case of a CD3 Negative Hepatosplenic T-Cell Lymphoma: Diagnostic and Therapeutic Challenges - Laura Alder; Scott Graupner; Guanhua Lai; Victor Yazbeck (Case Reports in Hematology)
Hepatosplenic T-cell lymphomas (TCLs) are a rare, aggressive subset of TCLs, accounting for less than 5% of all peripheral T-cell and natural killer (NK) cell lymphomas. We report the case of a CD3 negative hepatosplenic T-cell lymphoma in a 42-year-old female, who presented with left-sided abdominal pain. She underwent a liver biopsy that showed marked abnormal sinusoidal lymphoid infiltration. PET scan revealed increased splenic and pharyngeal lymph node uptake. Immunophenotype was remarkable for negative CD3, gamma delta T-cell receptor, and alpha beta-T-cell receptor expression. She received 6 cycles of DA-EPOCH, had primary refractory disease and then underwent palliative splenectomy secondary to painful necrosis. Then, she was started on pralatrexate as a single agent and then in combination with romidepsin as a potential bridge to an allogeneic stem cell transplantation from her sibling.